Features of the diagnosis and treatment of patients with AQP-4-positive neuromyelitis optica and MOG antibody disease - V. E. Avdeeva; A. S. Kotov (Русский журнал детской неврологии)
Background. As the amount of knowledge about multiple sclerosis increases, there is an interest in other forms of demyelinating diseases, among which neuromyelitis optica spectrum disorder and MOG (myelin oligodendrocyte glycoprotein) antibody disease can be distinguished.Objective: to improve the efficiency of diagnosis and treatment, to assess the long-term outcome in patients with AQP-4-positive neuromyelitis optica and MOG antibody disease.Materials and methods. The study included 14 patients: children, adolescents, adults, and elderly (9 - female, 5 -male). The duration of catamnesis ranged from 1 year to 6 years.Results and discussion. Antibodies to AQP-4 were found in 5 patients, antibodies to MOG were found in 9 patients. 89 % of patients with MOG antibody disease had the number of antibodies to MOG less than 50 pg/ml, determined by the Sandwich-type ELISA method; therefore, multiple sclerosis cannot be excluded (considering the oligoclonal IgG type 2 in three patients). To clarify the diagnosis, antibodies to MOG must be tested by more specific method of live cell-based assay in these patients.Based on this group of patients, it can be assumed that the younger the patient was, the earlier the diagnosis was made and treatment started, the better was prognosis. The prognosis was more favorable in patients with AQP-4-positive neuromyelitis in whom the disease debuted with optic neuritis. Patients with MOG antibody disease had a more favorable prognosis if the disease debuted with a supratentorial brain lesion; less favorable - when oligoclonal IgG type 2 was detected. Gender had no influence on the outcome of the disease.Conclusion. Differential diagnosis of this diseases based on clinical data is practically impossible. The study was carried out in a small group, so it is difficult to translate the results to the population of patients with neuromyelitis optica spectrum disorders. During treatment, almost all patients show positive dynamics when using glucocorticosteroids, human immunoglobulin preparations. Plasmapheresis was ineffective in patients with AQP-4-positive neuromyelitis optica, in some patients with MOG antibody disease the positive effect was observed. Cytostatic therapy was effective in patients with AQP-4-positive neuromyelitis optica. B cell depletion therapy with rituximab was effective in patients with MOG antibody disease. Interferon preparations did not give a positive effect.